Turkish adaptation of the Multidimensional Emotional Empathy Scale: A validity and reliability study - AŞTI, TÜRKINAZ; Turan N.; Durgun H.; Kaya H.; AŞTI T. (My University, 2021)
Purpose This study examined the validity and reliability of the Turkish version of the Multidimensional Emotional Empathy Scale for multidimensional evaluations of empathy. Design and Methods The methodological study included 202 nursing students. Turkish translation was performed using a back-translation technique. In determining the time invariance, the scale was applied twice to 38 nursing students with a 2-week interval, and the test-retest method was used, and intraclass correlations were calculated. Construct validity was examined with confirmatory factor analysis (CFA). Findings The content validity index was 0.997, and the general internal consistency coefficient of the scale was a highly reliable 0.905. With the CFA, it was determined that the fit index values were at an acceptable level and the model was suitable with this state. Practice Implications The Turkish version is considered a valid and reliable tool.
Keywords: Tıp; Hemşirelik; Sağlık Bilimleri; Medicine; Nursing; Health Sciences; HEMŞİRELİK; Klinik Tıp; Klinik Tıp (MED); Psikiyatri; NURSING; CLINICAL MEDICINE; Clinical Medicine (MED); PSYCHIATRY; Psikiyatrik Ruh Sağlığı; Farmakoloji (hemşirelik); Onkoloji (hemşirelik); Asistan Hemşirelik; Tıbbi ve Cerrahi Hemşirelik; Annelik ve Ebelik; LPN ve LVN; Acil Tıp Hemşireliği; Yoğun Bakım Hemşireliği; İleri ve Uzman Hemşirelik; Hemşirelik (çeşitli); Genel Hemşirelik; Psikiyatri ve Ruh Sağlığı; Psychiatric Mental Health; Pharmacology (nursing); Oncology (nursing); Nurse Assisting; Medical and Surgical Nursing; Maternity and Midwifery; LPN and LVN; Emergency Nursing; Critical Care Nursing; Advanced and Specialized Nursing; Nursing (miscellaneous); General Nursing; Psychiatry and Mental Health; empathy; nursing students; reliability; scale adaptation; validity; NURSING-STUDENTS